The transcription factor bZIP14 regulates the TCA cycle in the diatom Phaeodactylum tricornutum. (18th April 2017) - Matthijs, Michiel; Fabris, Michele; Obata, Toshihiro; Foubert, Imogen; Franco‐Zorrilla, José Manuel; Solano, Roberto; Fernie, Alisdair R; Vyverman, Wim; Goossens, Alain
Abstract: Diatoms are amongst the most important marine microalgae in terms of biomass, but little is known concerning the molecular mechanisms that regulate their versatile metabolism. Here, the pennate diatom Phaeodactylum tricornutum was studied at the metabolite and transcriptome level during nitrogen starvation and following imposition of three other stresses that impede growth. The coordinated upregulation of the tricarboxylic acid (TCA) cycle during the nitrogen stress response was the most striking observation. Through co‐expression analysis and DNA binding assays, the transcription factor bZIP14 was identified as a regulator of the TCA cycle, also beyond the nitrogen starvation response, namely in diurnal regulation. Accordingly, metabolic and transcriptional shifts were observed upon overexpression of bZIP14 in transformed P. tricornutum cells. Our data indicate that the TCA cycle is a tightly regulated and important hub for carbon reallocation in the diatom cell during nutrient starvation and that bZIP14 is a conserved regulator of this cycle. Synopsis: Oceanic algae can be metabolically re‐wired for lipid production. In the unicellular photosynthetic eukaryote P. tricornutum, the widely conserved transcription factor bZIP14 is linked to TCA cycle modulation upon reduced nitrogen availability and diurnal changes. Transcript and metabolite profiling analysis was performed during nitrogen starvation in the pennate diatom Phaeodactylum tricornutum . Co‐expression and functional analysis revealed a role for the bZIP14 transcription factor in the regulation of the TCA cycle. Upregulation of bZIP14 and TCA cycle expression is conserved in many diatoms. The bZIP14 transcription factor has a unique domain organisation and is conserved in both photosynthetic and heterotrophic heterokonts. Abstract : Oceanic algae can be metabolically re‐wired for lipid production. In the unicellular photosynthetic eukaryote P. tricornutum, the widely conserved transcription factor bZIP14 is linked to TCA cycle modulation upon reduced nitrogen availability and diurnal changes.